Effects of Perennial Fires on the Woody Vegetation of Mole National Park, Ghana (Journal of Science and Technology, 2016)
Recurrent fires have a considerable potential to influence the structure and composition of savanna vegetation. In Mole National Park in Ghana, the policy is to burn the vegetation annually early in the dry season. This study aimed to assess the effects of these perennial fires on the trees and shrubs of the Park. To achieve this, scars on tree bole bases as well as mortality and top-kill to trees ≥ 2 m tall resulting from perennial fires were assessed in twenty 50 m x 50 m plots in the savanna vegetation near Grupe camp at the south-western section of the Park. Fire scars on tree bole bases were widespread, but were significantly more frequent on large trees (> 5 m tall) than small ones (< 2 m tall). Also, certain tree species, notably Burkea africana and Detarium microcarpum were moreprone to scarring. The greater proportion of the scars had reached an advanced stage and the affected individuals were either moribund or were likely to be killed by subsequent fires or toppled by the wind. Contrary to the popular opinion that fire generally affects tree recruitment and not adult survival, fire-induced mortality and top-kill to large trees (> 5 m tall) was widespread among all the tree species, particularly Acacia dudgeoni, Burkea africana, Detarium microcarpum and Vitellaria paradoxa. These fire impacts will likely lead to changes in the relative abundance of the constituent tree species as well as a decline in the density of woody elements in the plant community as a whole unless burning frequency is reduced. The areas for which these predicted vegetation changes are valid can be generalized to include the vegetation in the northern half of the Park where similarconditions of high fuel load and intense fires are likely to prevail.